Ageing Workforce's Impact on Modern Organizations: How to Extend Working Lives? - Katja Debelak; Barbara Grah; Sandra Penger (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2023)
The ageing workforce is a growing concern for modern organisations as the proportion of older workers in the labour force continues to increase. This phenomenon has significant implications for the functioning and performance of organisations. On the one hand, older workers bring valuable skills and experience to the workplace, which can benefit the organisation. However, on the other hand, the ageing workforce also poses several challenges, including issues related to health, productivity, and retirement. This paper examines the impact of an ageing workforce on modern organisations. The paper aims to provide a comprehensive understanding of the demographic trends driving the ageing of the workforce and the potential benefits and challenges that an ageing workforce presents to organisations. The methodology used in this paper is a literature review of existing research on the ageing workforce and its impact on organisations. The literature review is conducted to identify key trends, patterns, and themes related to the ageing workforce and its impact on organisations. In conclusion, the paper also points out that the ageing workforce is a complex issue that presents benefits and challenges for modern organisations. Therefore, organisations must develop strategies to manage the ageing workforce that are inclusive and effective, support and retain older workers, and ensure their business's long-term success.
Keywords: J14; J24; J26; J28; J5; J62; 330; ageing; organisational development; age-management; HR strategy; working life